The impact of 360-degree feedback on innovative behavior within the organization: the mediating role of organizational justice - Souki, Karen (2024)
Purpose This study aims to examine organizational justice, innovation and 360-degree feedback appraisals. It examines how 360-degree feedback appraisals affect innovative behavior, execution and creative asset use. This paper examines organizational justice (distributive, procedural and interactional) and employee perceptions of 360-degree feedback systems. Finally, this study investigates how procedural and interactional justice mediate the relationship between innovative behavior and 360-degree feedback appraisals. Design/methodology/approach A sample of 200 participants from diverse locations, including Lebanon, Europe, the GCC, North Africa and Australia, spanning various occupations and industries were asked to complete the survey. This sample targeted participants who would be interested in the topic and who were selected from a diverse demographic characteristic. The Statistical Package for the Social Sciences software was used to analyze the research data. Findings This study reveals important connections within organizations. It shows a positive link between using 360-degree feedback appraisals and innovation, including idea generation and implementation. In addition, it confirms that using such feedback is linked to employees' perceptions of fairness. Moreover, it finds a positive connection between innovation and fairness. Finally, it highlights organizational fairness as a key mediator between 360-degree feedback and innovation. Research limitations/implications The recent investigations conducted exhibit various limitations that open avenues for prospective research. Initially, a cross-sectional design was used, presenting an opportunity for future research to consider adopting a longitudinal approach. This method could facilitate the collection and analysis of data over time, allowing for a more nuanced exploration of causality. Moreover, this research concentrated solely on a singular component of performance appraisal, namely, 360-degree feedback. To enrich future investigations, researchers are encouraged to encompass other facets of performance appraisal, such as gauging satisfaction with and the efficacy of performance appraisal. Furthermore, potential future studies may delve into exploring the mediating impact of other variables in the relationship between 360-degree feedback and innovative behavior, such as job satisfaction and affective commitment. In addition, the potential role of various moderating variables, including organizational culture, perceived organizational support and structural empowerment, could be investigated in forthcoming studies. Practical implications The study's findings carry practical implications for various stakeholders, encompassing employees, managers and policymakers. Managers aiming to foster an innovative culture should meticulously craft a 360-degree evaluation system that recognizes and incentivizes both concrete and intangible manifestations of innovation. The examination conducted in this research suggests a robust correlation between the existence of a 360-degree evaluation and behaviors related to ideation, encompassing idea generation and implementation. Social implications To cultivate innovative behavior among employees, managers should empower their workforce, and one effective approach is to enhance employees' perceptions of the quality of performance appraisals. Recognizing employee innovative behavior emerges as a crucial prerequisite for the growth, development and sustainability of organizations, demanding specific attention from both managers and policymakers. In the organizational context, the relationship between innovative behavior and perceptions of organizational justice shows that organizations should aim at fostering an atmosphere that promotes creativity while also ensuring fair treatment and recognition for contributors. Originality/value Despite the array of research on the relationship between innovative behavior and 360-degree feedback, this study is the first to examine the mediating effect of organizational justice on the relationship between 360-degree feedback and innovative behavior.